(untitled) (Revista Estudios Psicológicos, 2022)
The aim of the present study was to identify, by means of a systematic review, the most frequent predictors of alcohol consumption in adolescents. To this end, a search for articles was carried out in different databases, such as PsycINFO, Web of Science and Scopus. A total of 341 documents were obtained and, after applying the established inclusion criteria, 14 papers remained for review. The results showed different predictors of alcohol intake by adolescents. In particular, drinking alcohol at an early age, parental consumption, the presence of little family support, the establishment of relationships with peers with a tendency towards consumption, maintaining a poor relationship with the mother figure, showing low levels of intelligence, self-esteem and self-efficacy, as well as smoking, the search for new sensations, having positive expectations towards alcohol, having a permissive attitude towards alcohol intake on the part of parents, having economic availability, watching televised soccer games and, finally, having sexual relations at an early age. Consequently, it is recommended that new intervention programs take into account the results of the present study. In conclusion, it is suggested that new studies should be carried out to verify these findings in order to improve the quality of life of adolescents.